Cellular senescence induces replication stress with almost no affect on DNA replication timing. Issue 13 (3rd July 2018) - Rivera-Mulia, Juan Carlos; Schwerer, Hélène; Besnard, Emilie; Desprat, Romain; Trevilla-Garcia, Claudia; Sima, Jiao; Bensadoun, Paul; Zouaoui, Anissa; Gilbert, David M.; Lemaitre, Jean-Marc
ABSTRACT: Organismal aging entails a gradual decline of normal physiological functions and a major contributor to this decline is withdrawal of the cell cycle, known as senescence. Senescence can result from telomere diminution leading to a finite number of population doublings, known as replicative senescence (RS), or from oncogene overexpression, as a protective mechanism against cancer. Senescence is associated with large-scale chromatin re-organization and changes in gene expression. Replication stress is a complex phenomenon, defined as the slowing or stalling of replication fork progression and/or DNA synthesis, which has serious implications for genome stability, and consequently in human diseases. Aberrant replication fork structures activate the replication stress response leading to the activation of dormant origins, which is thought to be a safeguard mechanism to complete DNA replication on time. However, the relationship between replicative stress and the changes in the spatiotemporal program of DNA replication in senescence progression remains unclear. Here, we studied the DNA replication program during senescence progression in proliferative and pre-senescent cells from donors of various ages by single DNA fiber combing of replicated DNA, origin mapping by sequencing short nascent strands and genome-wide profiling of replication timing (TRT). We demonstrate that, progression into RS leads to reduced replication fork rates and activation of dormant origins, which are the hallmarks of replication stress. However, with the exception of a delay in RT of the CREB5 gene in all pre-senescent cells, RT was globally unaffected by replication stress during entry into either oncogene-induced or RS. Consequently, we conclude that RT alterations associated with physiological and accelerated aging, do not result from senescence progression. Our results clarify the interplay between senescence, aging and replication programs and demonstrate that RT is largely resistant to replication stress.